Ubiquitin C-Terminal Hydrolase L5 (UCHL5) Accelerates the Growth of Endometrial Cancer via Activating the Wnt/β-Catenin Signaling Pathway - Liu, Da; Song, Zixuan; Wang, Xiaoying; Ouyang, Ling (Frontiers in Oncology, 2020)
Endometrial cancer (EC) is the most common gynecological malignancy with high mortality. Chemotherapy plays an important role both in an adjuvant setting and in exclusive treatment. However, current pharmacotherapies are limited and not ideal to improve overall survival. Thus, identification of the molecular mechanisms responsible for initiation and progression of EC is imperative for developing novel therapeutic strategies. Ubiquitin C-terminal hydrolase L5 (UCHL5) has been reported to aggravate tumor growth and metastasis in mice bearing various types of cancer cells such as esophageal squamous cell carcinoma, hepatocellular carcinoma, and epithelial ovarian cancer. However, whether UCHL5 influences the growth of EC has not been elucidated. To expose the role of UCHL5 on EC, bioinformatics analysis was conducted and hinted that UCHL5 was overexpressed in EC tissues and associated with lower overall survival. Consistently, the overexpression of UCHL5 in EC tissues and cell lines was further confirmed by western blot (WB) and Polymerase Chain Reaction (PCR) compared with non-tumor control. Lentivirus vectors carrying UCHL5 shRNA or CDs sequences were used to reduce or overexpress UCHL5 gene, respectively. Cell proliferation and cycle were facilitated and cell apoptosis was decreased when UCHL5 gene was overexpressed in EC cell lines. These results were opposite in UCHL5 knockdown EC cells. Additionally, the expression of β-catenin is positively related to UCHL5 levels and the tumorigenic effects of UCHL5 overexpression were reversed by a Wnt/β-catenin pathway inhibitor XAV939. Thus, Wnt/β-catenin pathway activation may be partial mechanism responsible for the promoting effects of UCHL5 on EC growth. In conclusion, UCHL5 accelerated the growth of EC via Wnt/β-catenin pathway and was expected to be an attractive target for EC treatment.